Experiences and expectations of nurses in caring for organ donors and their families - Moraes, Edvaldo Leal de; Neves, Fabrício Ferreira; Santos, Marcelo José dos; Merighi, Miriam Aparecida Barbosa; Massarollo, Maria Cristina Komatsu Braga (Revista da Escola de Enfermagem da USP, 2015)
Objective Understand the experiences and expectations of intensive care unit nurses in caring for organ donors and their families. Method Qualitative research, with a social phenomenological approach, conducted in 2013 with 20 nurses. Results The experiences of the nurses with the families of donors were represented by two categories: obstacles encountered and interventions performed in the care of the donors’ families. The expectations of these professionals in caring for organ donors and their families were described in the category: care to save lives. Conclusion The study showed that the day-to-day work of intensive care nurses in their care of organ donors and their families is permeated with obstacles that interfere in the donation process. In light of this, their goal is to provide intensive care to deceased donors and humanized care to the families, to help family members agree to organ donation and enable organs to be made available for transplants.